Dominance and competence face to face: Dissociations obtained with a reverse correlation approach. (19th February 2019) - Oliveira, Manuel; Garcia‐Marques, Teresa; Dotsch, Ron; Garcia‐Marques, Leonel
Abstract: The article explores whether the traits representing the dimensions underlying the structure of facial and non‐facial impressions are similarly mapped in the face space. Two studies examine whether the trustworthiness‐by‐dominance and the warmth‐by‐competence two‐dimensional models overlap in face perception. In Study 1 ( N  =   200), we used a reverse‐correlation task to obtain classification images (CIs) reflecting how each dimension is mapped onto a face. Results show that the similarity between CIs was higher between warmth and trustworthiness than between competence and dominance. In Study 2 ( N  =   31) the evaluations of each CI on each social dimension show a higher dissociation between dominance and competence than between trustworthiness and warmth. These results, obtained at both perceptual and judgment levels, suggest that there is only a partial correspondence between the two models that seems to be driven by the relationship that the competence and dominance dimensions establish with valence.